Implementasi Algoritma C 4.5 Untuk Pendeteksi Banjir Berbasis IOT - Romi (CV. Multi Kreasi Media, 2023)
Indonesia is a country that has a tropical climate. People should be more aware of flood disasters. As a result of the flood disaster, many losses were caused and even many people lost their lives. Losses occur because residents are less prepared for disasters that will occur. Therefore, an effort is needed to minimize the loss of life and losses that occur by designing a flood detection system to monitor the water level. This system is based on IoT (Internet of Things) which refers to a network that connects various physical devices with different protocols. This flood detection system uses a water level sensor to detect the water level, a turbidity sensor to detect water turbidity, the NodeMCU ESP8266 to read data and send it via the internet and a buzzer that functions to make a sound when the sensor detects water and has the potential to flood. The system will work automatically when the water touches the sensor by sending flood detection status information. This system will later be implemented for the community in various flood-prone areas.